I rapporti fra città e campagna allo specchio della normativa statutaria un confronto fra lo Stato della Chiesa, la Toscana e l'Abruzzo (secoli XII-XVI) - Scharf, Gian Paolo Giuseppe (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2022)
During late Middle Ages the space corresponding to Papal State showed some features similar to those of Central-Northern Italy, sharing others with the Southern Kingdom. This interesting mix can be tested observing statutory law, that, regarding this period, has abundantly survived, although revealing remarkable regional differences. The interplay between cities and villages in this situation is complicated by Papal power, which participates in that relationship, affecting it with a varying intensity and continuity. In this book we try to specify the "three parts game" that happened during the legislative process, considering also other players action, such rural lords. The work includes four essays about the four lands forming the Papal State and other three about nearer lands, i.e. Florentine Tuscany, Siennese one and the Sicilian Kingdom (reserving a special attention at Abruzzo), and suggests useful comparisons, one of the project paramount aims. The scholars invited to join the enterprise, each specialist of a single land, during their research considered other's results, notwithstanding the physical distance among each other. Thus, we try to offer a homogeneous picture, at least regarding powers interplay dynamics.